The effect of a gearshift interlock on seat belt use by drivers who do not always use a belt and its acceptance among those who do. (June 2018) - Kidd, David G.; Singer, Jeremiah; Huey, Richard; Kerfoot, Laura
Abstract: Introduction: Seat belts reduce the risk of fatal injury in a crash, yet in 2015, nearly 10, 000 people killed in passenger vehicles were unrestrained. Enhanced seat belt reminders increase belt use, but a gearshift interlock that prevents the vehicle from being placed into gear unless the seat belt is used may prove more effective. Method: Thirty-two people with a recent seat belt citation and who admitted to not always using a seat belt as a driver were recruited as part-time belt users and asked to evaluate two new vehicles. Sixteen drove two vehicles with an enhanced reminder for one week each, and 16 drove a vehicle with an enhanced reminder for one week and a vehicle with a gearshift interlock the following week. Sixteen full-time belt users who reported always using a seat belt drove a vehicle with a gearshift interlock for one week to evaluate acceptance. Results: Relative to the enhanced reminder, the gearshift interlock significantly increased the likelihood that a part-time belt user used a belt during travel time in a trip by 21%, and increased the rate of belt use by 16%; this effect approached significance. Although every full-time belt user experienced the gearshift interlock, their acceptance of the technology reported in a post-study survey was fairly positive and not significantly different from part-time belt users. Six part-time belt users circumvented the gearshift interlock by sitting on a seat belt, waiting for the system to deactivate, or unbuckling during travel. Conclusion: The gearshift interlock increased the likelihood that part-time belt users buckled up and the rate of belt use during travel relative to the enhanced reminder but could be more effective if it prevented circumvention. Practical applications: An estimated 718–942 lives could be saved annually if the belt use of unbuckled drivers and front passengers increased 16–21%. Highlights: Belt use of 32 part-time belt users and 16 full-time users was recorded for 2 weeks. Half of the part-time users and every full-time user experienced a gearshift interlock. Belt use rate among part-time users with the interlock increased 16%. A 16% increase in belt use would save an estimated 718 lives annually. Most full-time belt users thought the gearshift interlock was acceptable.